Household status and socio-economic determinants of divorce among married women in Nigeria: a pooled data analysis - Dorothy N. Ononokpono; Nebechukwu H. Ugwu; Clifford O. Odimegwu (Cogent Social Sciences, 2025)
Divorce cases among married women have increased substantially, particularly in developed countries. Despite the perceived benefits of being married, divorce among married women continues to rise in Nigeria. In this study, we aim to explore trends in divorce cases, household status, and their associated factors among married women aged 15–49 years in Nigeria. Data pooled from the 2008, 2013, and 2018 Nigeria Demographic and Health Surveys were used for this study. The survey was nationally representative and conducted among women nationwide. A total of 116,795 ever-married women were included in the analysis. Bivariate and multivariate logistic regression analysis was done to identify the household socioeconomic determinants of divorce among married women in Nigeria. p-value <0.05 was used to declare statistical significance. The results show a significant increase in divorce cases among married women from 17.0% in 2008 to 60.4% in 2018. About 16% of non-educated women and those in middle-income and poor households substantially experienced divorce. Only 9.4% of unemployed women from poor households and 6.9% of unemployed women from middle-income households had experienced divorce or separation. Women with experience of physical violence [aOR = 5.22, 95% CI: 4.65–5.87], who experienced sexual violence [aOR = 3.29, 95% CI: 2.85–1.80], were more likely to divorce or separate from their partners. Divorce among married women is increasing in Nigeria. Household socioeconomic factors were the key determinants of divorce cases. Addressing poverty and promoting education and employment opportunities may be important strategies for reducing divorce rates and strengthening families in Nigeria.